2020
DOI: 10.1002/nau.24334
|View full text |Cite
|
Sign up to set email alerts
|

Promoting and maintaining urinary continence: Follow‐up from a cluster‐randomized trial of elderly village women in Bangladesh

Abstract: Aims: Pelvic floor and mobility exercises were shown to be effective in managing incontinence in a cluster-randomized trial (CRT) of village women aged 60 to 75 years in Bangladesh. The present analysis examines continence 12 months after the CRT and exercise program implementation with village paramedics as preceptors.Methods: Women from nine villages in the exercise arm of the CRT were followed-up 12 months after the 6-month intervention. They provided information about exercise since the CRT and a 3-day con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…Many studies recognised the limited access to healthcare services in rural and remote areas particularly for the treatment and management of common chronic conditions like diabetes 32,33 . There were studies that indicated the limited access to services such as palliative care, general health clinics, mental health, and specialty health services 15,34,35 . Factors such as geographical isolation, 36 financial constraints, 30,37 transportation issues, 18,38 and lack of rural health facilities and healthcare staff 39,40 were identified as complicating access to healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies recognised the limited access to healthcare services in rural and remote areas particularly for the treatment and management of common chronic conditions like diabetes 32,33 . There were studies that indicated the limited access to services such as palliative care, general health clinics, mental health, and specialty health services 15,34,35 . Factors such as geographical isolation, 36 financial constraints, 30,37 transportation issues, 18,38 and lack of rural health facilities and healthcare staff 39,40 were identified as complicating access to healthcare.…”
Section: Resultsmentioning
confidence: 99%
“…In our programme, both PFMT and ExMI were followed by maintenance exercise to be performed over the whole follow‐up period. Such exercises are necessary for maintaining the ability of patients to promptly activate their pelvic muscles in situations at risk for urine leakages (e.g., sneezing, coughing, lifting heavy objects) 23 . In the present study, all patients in each group were taught the same exercises by a nurse specialist.…”
Section: Methodsmentioning
confidence: 96%
“…Such exercises are necessary for maintaining the ability of patients to promptly activate their pelvic muscles in situations at risk for urine leakages (e.g., sneezing, coughing, lifting heavy objects). 23 In the present study, all patients in each group were taught the same exercises by a nurse specialist. The exercises were derived from our previous programme 17 which had proven successful in fostering continence recovery.…”
Section: Aimmentioning
confidence: 99%
“…Most studies raised issues and difficulties encountered by older people in rural and remote areas. The main issues identified from the data were high rates of chronic diseases [23][24][25] and inadequate access to health care and social services [26][27][28][29][30]. These were linked to challenging characteristics of rural and remote communities, such as low health literacy [31], limited transportation [32], poverty [33], and unsafe neighbourhoods or environments [23].These all negatively impact the functional ability of older adults in relation to meeting basic needs, being mobile, and building and maintaining relationships.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study examined whether a multicomponent exercise programme based on independent home-training could enhance the cognitive function of older people [32]. There were two studies focusing on disease-specific symptoms related to physical functions [26,38]. Most studies (n = 13) reported significant improvements in physical functioning.…”
Section: Contribute To Societymentioning
confidence: 99%